Strike-slip tectonics in Arc-Continent collision: The Timor-Leste example - Dias, Rui (2012)
The general tectonic setting of Timor is generally well constrain and most authors agree with main tectonic units. These units could be followed from Flores / Savu longitude at west to the eastern Babar one; such continuity emphasize a monoclinic symmetry for more than 700 km.Recent detailed structural mapping at 1/25000 scale in Cribas region led to new data concerning, not only the geometry and kinematics of submeridian sinistral strike-slip fault system, but also emphasize its relation with the major E-W Cribas anticline.